Regional Tax and Levy Regulations After Law Number 1 of 2022 Concerning Financial Relations Between the Central Government and Regional Governments - Hadianing Sari, Bina; Amalia Putri Humairoh; Azalea Concita Dreifalia (Prodi Administrasi Publik FISIP UNPAS, 2024)
Artikel ini bertujuan untuk membahas pengaturan pajak dan retribusi daerah Pasca UU Nomor 1 Tahun 2022 tentang hubungan keuangan antara pemerintah pusat dan pemerintah daerah dengan menggunakan metode penelitian yuridis normatif. Hasil penelitian ini adalah Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan antara Pemerintah Pusat dan Pemerintah Daerah (UU HKPD) diharapkan dapat menjadi langkah awal dalam regulasi pajak dan retribusi daerah pasca UU HKPD. Regulasi ini memahami landasan perubahan regulasi terkait aspek tersebut serta memberikan lebih dalam tentang motivasi dan tujuan di balik penyesuaiannya. Hal ini bertujuan untuk meningkatkan otonomi dalam pemerintah daerah dianggap sebagai faktor dalam memperkuat akuntabilitas terutama dalam upaya meningkatkan pendapatan melalui pajak dan retribusi daerah. Maka, dengan adanya modifikasi regulasi mengenai pajak dan retribusi daerah sesuai dengan UU HKPD saat ini, diharapkan akan membawa dampak positif terhadap pengelolaan keuangan di tingkat pemerintah pusat dan daerah. Selain mencegah penurunan potensi pendapatan daerah, pembaharuan ini juga dimaksudkan untuk mengadaptasi potensi pendapatan daerah dengan UU HKPD dan kondisi saat ini, khususnya dalam hal penyesuaian tarif pajak dan retribusi daerah. Abstract This article aims to discuss the regulation of local taxes and levies after Law Number 1 of 2022 concerning financial relations between the central government and local governments by using normative juridical research methods. The result of this research is Law Number 1 of 2022 on Financial Relations between the Central Government and Local Governments (HKPD Law) is expected to be the first step in the regulation of local taxes and levies after the HKPD Law. This regulation understands the foundation of regulatory changes related to these aspects and provides more depth on the motivation and purpose behind the adjustments. The aim of increasing autonomy in local government is considered as a factor in strengthening accountability, especially in efforts to increase revenue through local taxes and levies. Thus, with the transfer of regulations regarding local taxes and levies in accordance with the current HKPD Law, it is expected to have a positive impact on financial management at the central and local government levels. Aside from preventing a decline in potential local revenues, this reform is also intended to adapt potential local revenues to the HKPD Law and current conditions, particularly in terms of adjusting local tax and levy rates.